2017
DOI: 10.1002/elps.201700144
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electrokinetic effects in insulator‐based dielectrophoretic systems

Abstract: Insulator-based dielectrophoresis (iDEP) has emerged as a powerful tool for multiple biomicrofluidic operations, such as cell separation and concentration. The key feature for iDEP systems is the alteration of insulating microchannel geometries to create strong electric field gradients. Under AC electric fields, this strong electric field gradient can affect fluid flow by (at least) two nonlinear electrokinetic phenomena; (a) electrothermal flow due to Joule heating and (b) induced charge electroosmosis (ICEO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
(92 reference statements)
0
33
0
Order By: Relevance
“…Recent experiments from the author's group have reported some astonishing results (with respect to those in Newtonian fluids), such as the oscillation of particle electrophoresis in the DC electroosmotic flow of viscoelastic fluids through a constriction microchannel and the wall‐directed particle migration in the DC electroosmotic flow of shear thinning fluids through straight rectangular microchannels . Future work in this direction may cover the study of how the fluid rheological properties affect the electrokinetic motion of particles in varying microchannels, and as well the development of numerical models for understanding such motions with efficient algorithms and appropriate constitutive equations. Joule heating and induced charge effects have been usually deemed detrimental to precise electrokinetic transport and placement of particles in microchannels because of the induced electrothermal and electroosmotic flows in high‐ and low‐conductivity fluids, respectively. However, recent studies from the author's group have demonstrated the feasibility of using each of these nonlinear electrokinetic flow circulations to enrich submicron particles, which may potentially be applied to the continuous concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent experiments from the author's group have reported some astonishing results (with respect to those in Newtonian fluids), such as the oscillation of particle electrophoresis in the DC electroosmotic flow of viscoelastic fluids through a constriction microchannel and the wall‐directed particle migration in the DC electroosmotic flow of shear thinning fluids through straight rectangular microchannels . Future work in this direction may cover the study of how the fluid rheological properties affect the electrokinetic motion of particles in varying microchannels, and as well the development of numerical models for understanding such motions with efficient algorithms and appropriate constitutive equations. Joule heating and induced charge effects have been usually deemed detrimental to precise electrokinetic transport and placement of particles in microchannels because of the induced electrothermal and electroosmotic flows in high‐ and low‐conductivity fluids, respectively. However, recent studies from the author's group have demonstrated the feasibility of using each of these nonlinear electrokinetic flow circulations to enrich submicron particles, which may potentially be applied to the continuous concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Joule heating and induced charge effects have been usually deemed detrimental to precise electrokinetic transport and placement of particles in microchannels because of the induced electrothermal and electroosmotic flows in high‐ and low‐conductivity fluids, respectively. However, recent studies from the author's group have demonstrated the feasibility of using each of these nonlinear electrokinetic flow circulations to enrich submicron particles, which may potentially be applied to the continuous concentration of nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For fluid electroosmosis, iDEP devices have thus far been almost entirely restricted to work with Newtonian fluids . The insulating structures can cause electrothermal flow and/or induced charge electroosmotic flow due to the amplified Joule heating in the fluid around them and their own electrical polarization, respectively . However, many of the chemical (e.g., colloidal suspensions and polymer solutions) and biological (e.g., blood, saliva, and DNA solutions) fluids are actually complex, exhibiting non‐Newtonian characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…Graphite particles are much more conductive and are thus experiencing positive DEP, even at much higher fluid electric conductivities than tested here. A small decrease of the separation efficiency at higher fluid conductivities is ascribed to thermal and electrothermal effects that are likely to interfere with the DEP trapping process [35], [36].…”
Section: B Scaling Laws In Porous Filter Materialsmentioning
confidence: 99%